PENGARUH MODAL SOSIAL DAN BUDAYA ORGANISASI TERHADAP KINERJA TENAGA MEDIS DI RSUD KABUPATEN KEPULAUAN TALAUD - Edy, Yosua Jaya; Maupa, Haris; Edy, Hosea Jaya (PHARMACON, 2013)
ABSTRACTThis study aims to analyze the direct effect of social capital factors and organizational cultureon the performance of medical personnel in hospitals Talaud Islands. The population in thisstudy is the Civil Servants (PNS) in Talaud Islands who served in hospitals Talaud Islands.Sampling technique in this study is proportional sampling with a sample size of 100 people.In the data analysis using Structural Equation Modelling (SEM), using AMOS program(Analysis of Moment Structure) 20. Structural Equation Modeling (SEM) is a multivariateanalysis technique that was developed to cover the limitations that are owned by the previousanalytical models that have been widely used in statistical research. Stuctural equation model(SEM) can be seen as a combination of factor analysis, path analysis, and regression. Theresults indicate that (1) Social Capital and significant positive effect on the performance ofmedical personnel in hospitals Talaud Islands (2) Organizational culture positive andsignificant impact on the performance of medical personnel in hospitals Talaud Islands.Keywords : Social capital, Organization Culture, Performance